Collaborative Problem-Solving Approach for Fostering Students’ Creativity in Physics Practicum - Saiyidah Mahtari; Arif Sholahuddin (Jurnal Penelitian Pendidikan IPA, 2025)
Creativity is a crucial competence in 21st-century science education; however, physics laboratory activities in higher education are still predominantly conducted using verification-based models, which provide limited opportunities for creative thinking development. This study aims to examine the effectiveness of a Collaborative Problem-Solving Laboratory (CPSL) approach in enhancing the creativity of prospective physics teachers. The study employed a pre-experimental one-group pre-test–post-test design involving 20 undergraduate students enrolled in a Basic Physics Practicum course. Students’ creativity was measured using an adapted Scientific Creativity Test encompassing fluency, flexibility, originality, and elaboration. Data were analyzed using the normalized gain (N-Gain) to determine the extent of improvement in each creativity indicator. The results revealed a substantial increase in students’ creativity after the implementation of CPSL. Three indicators—Unusual Uses, Problem Finding, and Product Improvement—achieved high N-Gain values (0.7–0.8), while Creative Imagination, Creative Experimental Ability, and Product Design showed moderate improvement (0.4–0.6). These findings indicate that integrating collaborative problem-solving processes throughout pre-laboratory, laboratory, and post-laboratory activities can effectively promote students’ creative thinking. It can be concluded that CPSL has the potential to transform physics laboratory practices from routine verification tasks into collaborative and creativity-oriented learning experiences.